Claim: If $g \circ f: A \to C$ is bijective then where $f:A \to B$ and $g:B \to C$ are functions then $f$ is injective and g is surjective. Also give an example where $g \circ f$ is bijective but $f$ is not surjective and $g$ is not injective.

Proof attempt:

Well if $g \circ f$ is bijective then $g \circ f$ is injective. Therefore $f$ is injective:

Suppose $$f(x)=f(y)$$

$$g(f(x))=g(f(y))$$ which means

$$(g \circ f)(x) = (g \circ f)(y)$$ since $g \circ f$ is injective we have $x = y$

Also if $g \circ f$ is bijective then $g \circ f$ is surjective and therefore $g$ is surjective

Suppose that $$g \circ f$$ is surjective take any $$y \in C$$

Since $$g \circ f$$ is surjective there exists an $$a \in A$$

such that $$(g \circ f)(a) =y$$ so

$$g (f(a)) = y$$ set

$$b=f(a) \in B$$ Then $$g(b)=g(f(a))=y$$

Therefore g is surjective.

firstly just to verify, my proofs answer the question right? Secondly is there a more direct and faster method?

Now for the second part:

$A = \{1\}, B=\{2,3\}, C\{4,5\}$

Define $f: A \to B$ as $f\{1\} \to \{2\}$ which is clearly not surjective because 3 is not mapped. Define $G\{2,3\} \to \{4,4\}$ Thus $g$ is not injective however my problem is that I don't think $f \circ g$ is bijective I just cannot figure out how to rectify a composition where one function is not surjective and the other is not injecitive and get a bijection


Your proof for $f$ being injective and $g$ being surjective are correct. For the counterexample, let $A = C = \{0\}$, $B = \{0,1\}$, and define $f$ such that $f(0) = 0$, and $g(0) = g(1) = 0$. Then clearly $f$ is not surjective and $g$ is not injective, but $g \circ f : \{0\} \to \{0\}$ with $g \circ f(0) = 0$ is clearly bijective.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.